Cytosolic Double-Stranded DNA as a Damage-Associated Molecular Pattern Induces the Inflammatory Response in Rat Pancreatic Stellate Cells: A Plausible Mechanism for Tissue Injury-Associated Pancreatitis - Taichi Nakamura; Tetsuhide Ito; Hisato Igarashi; Masahiko Uchida; Masayuki Hijioka; Takamasa Oono; Nao Fujimori; Yusuke Niina; Koichi Suzuki; Robert T. Jensen; Ryoichi Takayanagi (Hindawi Limited, 2012)
Pancreatitis is an inflammatory disease of unknown causes. There are many triggers causing pancreatitis, such as alcohol, common bile duct stone, virus and congenital or acquired stenosis of main pancreatic duct, which often involve tissue injuries. Pancreatitis often occurs in sterile condition, where the dead/dying pancreatic parenchymal cells and the necrotic tissues derived from self-digested-pancreas were observed. However, the causal relationship between tissue injury and pancreatitis and how tissue injury could induce the inflammation of the pancreas were not elucidated fully until now. This study demonstrates that cytosolic double-stranded DNA increases the expression of several inflammatory genes (cytokines, chemokines, type I interferon, and major histocompatibility complex) in rat pancreatic stellate cells. Furthermore, these increase accompanied the multiple signal molecules genes, such as interferon regulatory factors, nuclear factor-kappa B, low-molecular-weight protein 2, and transporter associated with antigen processing 1. We suggest that this phenomenon is a plausible mechanism that might explain how cell damage of the pancreas or tissue injury triggers acute, chronic, and autoimmune pancreatitis; it is potentially relevant to host immune responses induced during alcohol consumption or other causes.